A Study on the Relationship Among Psychological Resilience, Religious Coping and Life Satisfaction - (:unkn) unknown (DINBILIMLERI AKAD ARASTIRMA MERKEZI, 2015)
This article examines the relationship between psychological resilience, religious coping and life satisfaction among adults. Socio-demographic variables (gender, age, marital status etc.) are also examined in the study. Correlational survey method and questionnaire technique are used. The sample covers 512 individuals whose age range is from 18 to 59. Resilience Scale for Adults, Religious Coping Scale, and The Satisfaction with Life Scale are applied. The findings indicate that positive religious coping has positively correlated with life satisfaction and psychological resilience. Yet, negative religious coping does not have any relationship with these two variables. The other finding is that life satisfaction is rising with psychological resilience. According to regression analysis both positive religious coping and psychological resilience have positive effect on life satisfaction. Implications of these results and suggestions for future research are discussed.
Keywords: Psychological Resilience; Religious Coping; Life Satisfaction; Religiosity; Spirituality; Positive Psychology; WOMEN